EFFECT OF FAT ADDITION IN THE FINISHER RATION ON PERFORMANCE AND RATE OF FEED PASSAGE OF BROILERS - RAFH MOHAMMED TAHER (Mesopotamia Journal of Agriculture)
This experiment was conducted on 40 unsexed broiler chicks(ROSS) one day old to study the effect of using added fat (sunflower oil) in the finisher ration on some productive traits and rate of feed passage. The chicks were raised on floor in the first four weeks of age on starter ration with 2890 Kcal/kg ME and 22.43% CP .At four weeks of age 40 birds were selected randomly and distributed in single cages to four treatments with ten birds as replicates for each treatment .The four finisher rations 4 – 8 weeks were isoenergitic 3000Kcal/kg and protein 18% and different in the level of added fat 0 , 2 , 4 , 6 % . At the end of the experiment three birds of each treatment were slaughtered for carcass traits . The results showed that added fat have no significant effect on live body weight, daily weight gain , feed conversion ratio, growth rate, protein conversion ratio, dressing percentage, percentage of edible offal's, abdominal fat ,carcass parts , length of duodenum, intestine, cecum , and rate of feed passage ,while there was a significant effect on feed and protein consumption during 4-5 weeks (p≤0.01) and 6-7, 7-8 weeks (p≤0.05). Adding of 2 and 4% fat increased ration cost and decreased economic efficiency while 6% cause very simple improvement